ANALYSIS THE INFLUENCE OF PRODUCTION FACTORS ON THE LEVEL OF INCOME AT HANDICRAFT INDUSTRY AT PANTAI JOHOR VILLAGE DATUK BANDAR SUB-DISTRICT IN TANJUNG BALAI - Nasution, Nina Andriany (Accounting and Business Journal, 2019)
To accelerate the economy, Industrialization is required as a must because it ensures the continuity of the process of economic development with the pace of high economic growth and sustainable income-generating per capita each year. Industrialization is the root principle of national and regional development, which aims to create an advanced society and independent as well as prosperous and unseen. This study aims to determine the Factors of Production that affect the Level of Income On the Industrial Crafts in Pantai johor Village of Datuk Bandar subdistrict, Tanjung Balai. This study uses to approach the quantitative data with the model of multiple regression analysis. The results showed that the Independent Variables are Material Raw materials, Labor, Capital, Entrepreneurship in partial effect significant to the Dependent Variable i.e. the Level of Income on The Craft Industry. The next Variables simultaneously Independent, namely Raw Materials, Labor, Capital, Entrepreneurship significant effect on the Dependent Variable namely the Level of Income on the Industrial Crafts. The results of this research will be published in the scientific through Scientific journals Abdi Ilmu and the Journal of Accounting and Business that have the ISSN, as well as held a seminar on the implementation of the results of the study. It's also the making of the book as a material of teaching of additional subjects Public Sector Accounting, Financial Management, and Taxation.